ARCHAEOLOGY, NATIONALISM AND POLITICS IN SOUTHEAST ASIA - Glover, Ian C. (Hukay; Vol 3 No 1, 2014)
“Our experience of the present very largely depends oN our knowledge of the past.” (Connerton 1989: 2)